Properties of Chemically Stabilized Methanol–HVO Blends - Wang-Alho, Huaying; Sirviö, Katriina; Balogun, Fatimoh; Kaivosoja, Jonna; Nuortila, Carolin; Mikulski, Maciej; Niemi, Seppo (MDPI, 2024)
Approximately 25% of global carbon emissions come from food production. Renewable fuels are crucial for curbing greenhouse gas (GHG) emissions from vehicles, non-road machines, and agricultural machinery. Tractors, key to modern farming, are central to these efforts. As agriculture strives for sustainability, alternative fuels like methanol and hydrotreated vegetable oil (HVO) are arousing interest because they are renewable and offer potential for blending for use in diesel engines. Methanol and HVO have limited solubility in direct mixing, so the addition of a co-solvent is essential. This study addresses the research gap regarding the properties of HVO and methanol blends with co-solvents. It investigated the impact of three co-solvents, 1-dodecanol, 1-octanol, and methyl butyrate, on the miscibility of HVO and methanol. The experimental measurements cross-varied the co-solvent type with different blending ratios (MeOH5 and MeOH10). Investigated parameters include fuel density, kinematic viscosity, distillation properties, and surface tension. The co-solvents enabled the formation of a singular, clear, and homogeneous phase in methanol-HVO blends. The co-solvent 1-dodecanol demonstrated the highest solubilizing capacity for MeOH5 and MeOH10 blends, followed by 1-octanol. Adding co-solvents led to increased fuel density, decreased kinematic viscosity, and small changes in surface tension. These findings contribute to the optimization of methanol–HVO fuel blends for efficient and environmentally friendly use in vehicles, non-road machinery, and agricultural machinery.
Keywords: renewable fuels; hydrotreated vegetable oil (HVO); co-solvents; blending properties; methanol; fi=Energiatekniikka|en=Energy Technology|